STRATEGY FOR IMPROVING THE QUALITY OF ISLAMIC EDUCATION IN THE DIGITAL ERA - Farhan Azima; A. Latief Arung Arafah; Siti Patimah; Andi Warisno (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
Islamic education has an important role in forming a young generation who have faith, noble character and broad knowledge. In the current digital era, Islamic education needs to adapt to technological developments so that it can continue to provide quality education. There are several strategies that can be implemented to improve the quality of Islamic education in the digital era, such as increasing access to technology, developing the competence of teaching staff, creating quality Islamic learning content, utilizing digital technology for learning, and strengthening collaboration with various parties. Islamic education in the digital era face various challenges that need to be overcome. Improving the quality of Islamic education is the key to responding to these challenges and preparing the young generation who have faith, noble character and broad knowledge in the digital era. Improving the quality of Islamic education in the digital era can be done with strategies based on the Koran and Hadith. Utilizing digital technology, strengthening the role of teachers, instilling Islamic values, establishing cooperation and collaboration, and making the Koran and Hadith the main source of education are the keys to realizing superior Islamic education in the digital era.